2018
DOI: 10.1007/s10654-018-0388-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium and risk of incident heart failure in older men: The British Regional Heart Study

Abstract: To examine the association between serum magnesium and incident heart failure (HF) in older men and investigate potential pathways including cardiac function, inflammation and lung function. Prospective study of 3523 men aged 60–79 years with no prevalent HF or myocardial infarction followed up for a mean period of 15 years, during which 268 incident HF cases were ascertained. Serum magnesium was inversely associated with many CVD risk factors including prevalent atrial fibrillation, lung function (FEV1) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
2
13
1
4
Order By: Relevance
“…The overall results of this MR study did not find any evidence for a causal association between minerals and heart failure and thus do not support findings from previous observational studies, suggesting a positive association between serum calcium and heart failure risk (Lutsey et al, 2014) as well as an inverse association between serum magnesium and heart failure risk (Zhang et al, 2012; Lutsey et al, 2014; Kunutsor et al, 2016; Taveira et al, 2016; Wannamethee et al, 2018). However, given that previous studies are scarce and findings are limited by potential residual confounding and reverse causality, caution must be applied when interpreting these data.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The overall results of this MR study did not find any evidence for a causal association between minerals and heart failure and thus do not support findings from previous observational studies, suggesting a positive association between serum calcium and heart failure risk (Lutsey et al, 2014) as well as an inverse association between serum magnesium and heart failure risk (Zhang et al, 2012; Lutsey et al, 2014; Kunutsor et al, 2016; Taveira et al, 2016; Wannamethee et al, 2018). However, given that previous studies are scarce and findings are limited by potential residual confounding and reverse causality, caution must be applied when interpreting these data.…”
Section: Discussioncontrasting
confidence: 99%
“…However, findings are not consistent (Van-Hemelrijck et al, 2013; Donneyong et al, 2015). On the other hand and in line with findings for coronary artery disease, an inverse relationship has been suggested for blood levels and dietary intake of magnesium and heart failure incidence (Zhang et al, 2012; Lutsey et al, 2014; Kunutsor et al, 2016; Taveira et al, 2016; Wannamethee et al, 2018). However, due to the limited data available and the fact that most studies, with one exception (Donneyong et al, 2015), were observational, it is uncertain whether the associations are causal and not biased by reverse causality or residual confounding.…”
Section: Introductionsupporting
confidence: 59%
“…For additional EJE references please see [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160].…”
Section: Main Results In the Last 3 Yearsunclassified
“… 13 , 14 , 15 , 16 , 17 , 18 , 19 The available studies have also reported a significant association between imbalances in essential metals and CVD risk. Specifically, imbalanced levels of Zn, 20 , 21 Cu, 22 , 23 , 24 , 25 , 26 Cr, 27 , 28 Co, 29 , 30 Mg, 22 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 Se, 61 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ,…”
Section: Epidemiological Studies Linking Metal Exposures To Cvd Riskmentioning
confidence: 99%